Movements of tagged and radio-instrumented wild reindeer in relation to habitat alteration in the Snøhetta region, Norway - Skogland, Terje (Rangifer, 1986)
In winter, 1981, 103 reindeer, out of a population of 3600, were herded into a fence by snowmobiles and marked. During the next 4 1/2 years reindeer were followed from the ground, or by radiolocations from an airplane. On the average one animal was tagged per 42 animals in any group. A total sample of 175 locations in all seasons indicated that snow conditions, traffic on a road lying parallel to a railroad, and the damming of a lake significantly affected annual distribution as compared with expected modern as well as prehistoric distribution.